The dynamic coastal evidence of Jakarta Bay during Late Pleistocene-Recent. Issue 1 (December 2021) - Novico, F; Endyana, C; Menier, D; Mathew, M; Kurniawan, I; Bachtiar, H; Ranawijaya, D; Hendarmawan, H
Abstract: Some significant indication identifying a coastal dynamic during Late Pleistocene to Recent is the evolution of isochrone patterns throughout glacial-interglacial stages. This study aims to identify the sediments stratification of Jakarta Bay during the Late Pleistocene – Recent in the framework of coastal dynamic triggered by the sea-level changes of last prominent climatic stages. The several high-resolution seismic records in Jakarta Bay lines were interpreted to illustrate the different sequences from the top down to the oldest by line-drawing the more robust seismic reflectors as a sequence limit surface. Furthermore, the isochrone map series of unit boundary (UB) were reconstructed to delineate isochrone contour patterns from the oldest until modern. The selected isochrones map of UB-3 and UB-5 with their unit facies are somehow favorable to be compared for observing the coastal dynamic of Jakarta Bay during the last climatic variability. Finally, the coastal dynamic of Jakarta Bay is discovered by the movement series of isochrones contour patterns that correspond to the sea-level changes during the last prominent glacial-interglacial stages.